Experimental Study on Injection Molding of Wheat-Straw/High-Density Polyethylene Composites - Zhou, Yuanyuan; Li, Song (Asian Journal of Chemistry, 2012)
Now-days, most polymeric composites with natural fibers are typically processed by compression-molding. It is a challenge to embed natural fibers for manufacturing injection-molded parts. This study examined the feasibility of manufacturing wheat-straw flour and high-density polyethylene composites by employing injection molding method. The melt flow index (MFI) and thermal analysis (DSC and TGA) of composites with different wheat-straw flour contents were characterized. The tensile, flexural and impact properties of injection molded wheat-straw/high-density polyethylene samples were measured. It has been found that the melt points of composites were about 135ºC when wheat straw content was less than 30 wt %. In addition, the results show that the fluidity, tensile strength and impact strength of the composites decreased while the wheat-straw content increased. However, the flexural strength of the composites increased slightly with the increase in wheat straw flour content.